Tracking Algorithm for Augmented Reality System (International Journal of Engineering and Computer Science, 2017)
Augmented Reality(AR) aims at merging the real and the virtual in order to enrich a real environment with virtual information. Augmentations range from simple text annotations accompanying real objects to virtual environment of real life objects inserted into a real environment. In the latter case the ultimate goal is to make it impossible to differentiate between real and virtual objects. Several problems need to be overcome before realizing this goal. Amongst them are the rigid registration of virtual objects into the real environment. The key technology of Augmented reality includes displaying, registration and tracking, interactive, etc, among them , registration and tracking is most important technology. In this paper, we will demonstrate the algorithm for tracking a object from a real world and augmenting it on a virtual environment.